Genetics of the iron dicitrate transport system of Escherichia coli. - Pressler, U (1988)
Escherichia coli B and K-12 express a citrate-dependent iron(III) transport system for which three structural genes and their arrangement and products have been determined. The fecA gene of E. coli B consists of 2,322 nucleotides and encodes a polypeptide containing a signal sequence of 33 amino acids. The cleavage site was determined by amino acid sequence analysis of the unprocessed protein and the mature protein. For the processed form a length of 741 amino acids was calculated. The mature FecA protein in the outer membrane contains at the N terminus the "TonB box," a pentapeptide, which has hitherto been found in all receptors and colicins which functionally require the TonB protein. In addition, the dyad repeat sequence GAAAATAATTCTTATTTCG is proposed to serve as the binding site of the Fur iron repressor protein. The fecB gene was mapped downstream of fecA and encodes a protein with an apparent molecular weight of 30,000. It was synthesized as a precursor, and the mature form was found in the periplasm. The fecD gene follows fecB and was related to a membrane-bound protein with an apparent molecular weight of 28,000. In Mu d1 insertion mutants upstream of fecA, the fec genes were not inducible by iron limitation and citrate, indicating a regulatory region, termed fecI, which controls fec gene expression.